2023
DOI: 10.1186/s13287-023-03246-2
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of neural stem cell therapy for cerebral palsy: survey of the Australian cerebral palsy community

Abstract: Background Neural stem cells (NSCs) have the potential to engraft and replace damaged brain tissue, repairing the damaged neonatal brain that causes cerebral palsy (CP). There are procedures that could increase engraftment of NSCs and may be critical for efficacy, but hold notable risks. Before clinical trials progress, it is important to engage with the CP community to understand their opinions. The aim of this study was to determine the acceptability of NSC therapy for CP in the CP community.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…However, the lack of effective models has hindered more in-depth research ( 55 ). Although stem cell therapy is not currently widely used in children with CP, the parents of these children remain optimistic about the potential improvement of stem cell therapy, given the limited treatment options available for CP ( 56 ). Accordingly, stem cell treatments are worthy of exploration and may lead to breakthroughs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of effective models has hindered more in-depth research ( 55 ). Although stem cell therapy is not currently widely used in children with CP, the parents of these children remain optimistic about the potential improvement of stem cell therapy, given the limited treatment options available for CP ( 56 ). Accordingly, stem cell treatments are worthy of exploration and may lead to breakthroughs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The NSCs can be procured from brain tissue, reprogrammed from somatic cells, or differentiated from pluripotent stem cells, such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) 13,14 . They are also found in highly‐specific microenvironments, comprising cell and extracellular components, including ependymal cells, vasculature, extracellular matrix proteins, soluble factors, astrocytes, microglia, and pericytes 15 . While clinical trials in patients are still ongoing, preclinical research on the use of NSCs to treat neurological disorders has shown encouraging results 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…extracellular matrix proteins, soluble factors, astrocytes, microglia, and pericytes. 15 While clinical trials in patients are still ongoing, preclinical research on the use of NSCs to treat neurological disorders has shown encouraging results. [16][17][18] The studies conducted in vitro or using animal models have demonstrated that NSCs can be stimulated and activated to differentiate into neurons, thus replacing lost neurons, and also enhance the local microenvironment, promote the growth of blood vessels, adjust inflammatory responses, and restore the homeostasis of the brain.…”
mentioning
confidence: 99%
“…The remarkable migratory ability of neural stem cells (NSCs) to integrate into damaged areas of the brain provides strong preclinical evidence for the treatment of children with perinatal brain injury (6). It brings hope for neuroregeneration in patients with CP (7,8). In recent years, many scholars have proven the safety and early efficacy of NSCs clinical trials and have focused on further clinical translation (9,10).…”
mentioning
confidence: 99%